2018
DOI: 10.1177/1557988318768597
|View full text |Cite
|
Sign up to set email alerts
|

USPSTF Testicular Examination Nomination–Self-Examinations and Examinations in a Clinical Setting

Abstract: In 2004, the U.S. Preventive Services Task Force (USPSTF) published a Grade D recommendation for both testicular self-examination (TSE) and clinical evaluation to screen for testicular cancer in asymptomatic males. This review committee reaffirmed these recommendations in 2009 and again in 2011 (Testicular Cancer: Screening Release Date: April 2011. Final Update Summary: Testicular Cancer: Screening. U.S. Preventive Services Task Force. September 2016). The 2011 USPSTF review found no significant evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…The most common symptom is a mass in the testis in the early period, but in many patients, there is widespread pain, swelling, or stiffness in the scrotum [ 8 ]. Acute testicular pain is less frequent and is more often caused by the testis’ swift expansion owing to intratumor hemorrhage or infarction [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptom is a mass in the testis in the early period, but in many patients, there is widespread pain, swelling, or stiffness in the scrotum [ 8 ]. Acute testicular pain is less frequent and is more often caused by the testis’ swift expansion owing to intratumor hemorrhage or infarction [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the National Cancer Institute and the U.S. Preventive Service Task Force do not recommend TC screening due to inadequate evidence confirming its detection power, while data from the American Cancer Society or Cancer Research UK endorse a screening method to support early TC detection (). Although the risk and benefits for testicular self-examination (TSE) are debatable, this method can potentially help to diagnose TC at the early stage 8 – 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The man is taught to perform the TSE when the scrotum is soft and relaxed, usually after a shower. In addition, TSE is recommended to be done at least once a month starting at the onset of puberty [17]. TSE teaching begins when the man becomes familiar with the major structures of the testis, scrotum, testicle, and epididymis [86].…”
Section: The Importance Of Early Detection Of Tc and Tsementioning
confidence: 99%
“…As with breast cancer, early detection of TC is best done through self-examination [16]. Although routine screening and monthly self-examination in young men have been recommended, studies have not shown that they improve outcomes [17].…”
Section: Introductionmentioning
confidence: 99%